2021
DOI: 10.1038/s41388-020-01604-5
|View full text |Cite
|
Sign up to set email alerts
|

A feed-forward loop between SorLA and HER3 determines heregulin response and neratinib resistance

Abstract: Current evidence indicates that resistance to the tyrosine kinase-type cell surface receptor (HER2)-targeted therapies is frequently associated with HER3 and active signaling via HER2-HER3 dimers, particularly in the context of breast cancer. Thus, understanding the response to HER2-HER3 signaling and the regulation of the dimer is essential to decipher therapy relapse mechanisms. Here, we investigate a bidirectional relationship between HER2-HER3 signaling and a type-1 transmembrane sorting receptor, sortilin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
(56 reference statements)
1
25
0
1
Order By: Relevance
“…According to Pietilä et al (2019) , the depletion of SORL1 triggers HER2 accumulation in dysfunctional lysosomes, and SORL1 -silenced cells showed antiproliferative effects on not only breast cancer but also bladder cancer by regulating oncogenic receptor tyrosine kinase (RTK) signaling. This group further investigated the role of SORL1 in mediating targeted therapy resistance in breast cancer and discovered that SORL1 is necessary for HER2-HER3-driven oncogenic cell growth ( Al-Akhrass et al, 2021 ). However, Michael et al (2019) discovered that the downregulation of SORL1 expression facilitates tumor growth in a transplant tumor model and relatively low expression predicts a worse prognosis in human breast, lung, and gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pietilä et al (2019) , the depletion of SORL1 triggers HER2 accumulation in dysfunctional lysosomes, and SORL1 -silenced cells showed antiproliferative effects on not only breast cancer but also bladder cancer by regulating oncogenic receptor tyrosine kinase (RTK) signaling. This group further investigated the role of SORL1 in mediating targeted therapy resistance in breast cancer and discovered that SORL1 is necessary for HER2-HER3-driven oncogenic cell growth ( Al-Akhrass et al, 2021 ). However, Michael et al (2019) discovered that the downregulation of SORL1 expression facilitates tumor growth in a transplant tumor model and relatively low expression predicts a worse prognosis in human breast, lung, and gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that SORLA, through interactions at its extracellular domain, exists in a complex with HER2 and co-tra cs with HER2, facilitating HER2 recycling to the plasma membrane to support HER2 downstream signalling. In the absence of SORLA, HER2 becomes localized to enlarged, partially dysfunctional lysosomes, resulting in defective HER2 signalling and increased sensitivity [16,17]. Increasing evidence indicating the important roles that Sortilin and SorLA participate in a variety of tumour progression-related processes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the methods employed in this study are the same as those described in our earlier publications [ 18 , 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…The mature SorLA protein resides mainly in the trans‐Golgi network and undergoes constitutive antero‐ and retrograde trafficking to the plasma membrane through endosomes. Due to its central role in protein trafficking, SorLA has been implicated in the development and/or progression of neurological and metabolic diseases and most recently in cancer [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation